Miastenia Gravis Okular Juvenil: Laporan Kasus - Fikta Zakia Nurfaizah (Jurnal Ilmu Medis Indonesia, 2021)
Purpose: This study aimed to summarize the general history, physical exam findings, confirmation test, and treatment of a patient with juvenile ocular myasthenia gravis. Research Methodology: This article is a pediatric RSUD Abdoel Moeloek Lampung case report in April 2021. The subject of the case is a 3-year-old girl who is hospitalized in the hospital ward with juvenile ocular myasthenia gravis. Result: A 3-year-old girl, an inpatient in the Pediatric Ward, RSUD Abdoel Moeloek Lampung, with complaints of decreased left upper eyelid since three months ago. On physical examination, there was ptosis of the left superior palpebra. Prostigmine test was performed on day 2 of treatment in patients with positive test results. The patient was clinically diagnosed with “Juvenile Ocular Myasthenia Gravis.” Management of the patient during treatment was the injection of methylprednisolone 10 mg/12 hours and neostigmine orally 2.5 mg/8 hours. Limitations: This case report is limited to juvenile ocular myasthenia gravis cases with a scarce number of cases and rare cases in children. Contribution: This case report can be helpful in medical education or used as a reference in making relevant case reports and can be applied in the hospital area when there are cases of juvenile ocular myasthenia gravis.